ASMOSIA : Association for the Study of Marble & other Stones in Antiquity - Association for the Study of Marble and Other Stones Used in Antiquity (2003)
[Dt.:] Auf der Seite stellt sich ASMOSIA vor, eine Gesellschaft zur Erforschung von Marmor und anderen Gesteinsarten in der Antike. Es wird über aktuelle Projekte informiert, es gibt einen Newsletter und die Möglichkeit, Mitglied der Gesellschaft zu werden. - [Engl.:] The site presents ASMOSIA, the association for the study of marble and other stones in antiquity. It informs on current projects, there is a newsletter and the possibility to become a member of the association.